The role of KLF4 in human primordial germ cell development - Sun-Min Lee; Merrick Pierson Smela; M. Azim Surani (Open Biology)
Primordial germ cells (PGCs) are the founder cells that develop into mature gametes. PGCs emerge during weeks 2–3 of human embryo development. Pluripotency genes are reactivated during PGC specification, including Krüppel-like factor KLF4, but its precise role in PGC development is unclear. Here, we investigated the role of KLF4 in PGC development using our in vitro model for human PGC-like cells (hPGCLCs). We demonstrate that the depletion of KLF4 reduces the efficiency of hPGCLC specification, resulting in hPGCLCs with an aberrant transcriptome. Cut-and-run and transcriptomic analyses reveal that KLF4 represses somatic markers involved in neuronal and endodermal differentiation while promoting the expression of genes associated with PGC specification, such as PAX5, and epigenetic regulators, including DNMT3L and REST. KLF4 targets in hPGCLCs showed significant co-enrichment of motifs for SP and STAT factors, which are known to regulate cell cycle and migration genes. KLF4 contributes to human PGC development by activating genes involved in PGC specification and cell cycle regulation, while repressing somatic genes to maintain PGC identity.